2009
DOI: 10.1097/mpg.0b013e31818eb8de
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association Between Helicobacter pylori and Gastroesophageal Reflux Disease in Children

Abstract: Objectives-The role of Helicobacter pylori (H. pylori) in gastroesophageal reflux disease (GERD) remains controversial, particularly in children, since there are limited published data. Adult studies suggested that H. pylori infection may protect against GERD by causing atrophic gastritis, which leads to reduced gastric acid secretion. The objective of our study was to determine the role of H. pylori infection in the development of GERD in a pediatric population.Methods-A retrospective analysis of 420 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
(73 reference statements)
1
21
0
1
Order By: Relevance
“…Positive H. pylori status has been shown to be associated with a lower risk of EE [45]. One study showed that H. pylori eradication was associated with presence of EE [51]; other studies showed contradictory findings [52,53]. Our study though performed in a subset of patients considered acid related as well as motility parameters.…”
Section: Discussionmentioning
confidence: 72%
“…Positive H. pylori status has been shown to be associated with a lower risk of EE [45]. One study showed that H. pylori eradication was associated with presence of EE [51]; other studies showed contradictory findings [52,53]. Our study though performed in a subset of patients considered acid related as well as motility parameters.…”
Section: Discussionmentioning
confidence: 72%
“…(1) Some researchers have pointed out negative correlation of GERD with Helicobacter pylori infection, (34,35) while others reported no or positive correlation. (3638) Since we did not perform endoscopy nor Helicobacter pylori examination in this study, it is unclear whether patients with these conditions were included in our study and whether they associated with GERD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…23 On the other hand, some studies have shown that H. pylori infection increases the risk of GORD in children. [24][25][26] Daugule et al showed that the prevalence of H. pylori is significantly higher in children with GORD than in children with hyperaemic gastropathy alone. 24 Studies in adults and children have shown that H. pylori-positive patients have a denser and more severe infection in the antrum.…”
Section: Discussionmentioning
confidence: 99%